2019
DOI: 10.1152/japplphysiol.00344.2019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of priming exercise on oxygen uptake and muscle deoxygenation kinetics during moderate-intensity cycling in type 2 diabetes

Abstract: The pulmonary oxygen uptake (V̇o2) kinetics during the transition to moderate-intensity exercise is slowed in individuals with type 2 diabetes (T2D), at least in part because of limitations in O2 delivery. The present study tested the hypothesis that a prior heavy-intensity warm-up or “priming” exercise (PE) bout would accelerate V̇o2 kinetics in T2D, because of a better matching of O2 delivery to utilization. Twelve middle-aged individuals with T2D and 12 healthy controls (ND) completed moderate-intensity con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 74 publications
(65 reference statements)
3
15
0
Order By: Relevance
“…It is possible that the high rates or 'steps' of muscle fiber recruitment and repetitive shear stress during the HIIT exercise sessions influenced the current outcome (39). However, it remains unclear why a levelling off in the V ̇O2 kinetics When applying this measure simultaneously with V ̇O2 kinetics measurements, our laboratory recently showed that the rate of adjustment in the NIRS-derived [HHb+Mb] was faster than the adjustment in τV ̇O2p in uncomplicated T2D, suggesting an over reliance in fractional oxygen extraction and thus, a reduced blood flow response (66). Findings in keeping with T2D-induced impairments in the dynamic response of vasodilation and matching of capillary blood flow to metabolism in contracting myocytes (30,38,57,58,60).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the high rates or 'steps' of muscle fiber recruitment and repetitive shear stress during the HIIT exercise sessions influenced the current outcome (39). However, it remains unclear why a levelling off in the V ̇O2 kinetics When applying this measure simultaneously with V ̇O2 kinetics measurements, our laboratory recently showed that the rate of adjustment in the NIRS-derived [HHb+Mb] was faster than the adjustment in τV ̇O2p in uncomplicated T2D, suggesting an over reliance in fractional oxygen extraction and thus, a reduced blood flow response (66). Findings in keeping with T2D-induced impairments in the dynamic response of vasodilation and matching of capillary blood flow to metabolism in contracting myocytes (30,38,57,58,60).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms governing the impaired τV ̇O2P herein are not well understood, they are likely influenced, at least partly, by cardiovascular defects, for example impaired left ventricular filling (83,84), and/or limitations in peripheral O 2 delivery/supply to contracting muscles in the lower limbs (8,30,31,34,38,59), although restrictions in the oxygen extraction ability have also been reported (29,65). Our laboratory recently showed a larger mismatch in local (microvascular) O 2 delivery to utilization in the quadriceps muscle in T2D compared with healthy controls, which was accompanied with slowed τV ̇O2p (66). This was reflected by a greater ratio of change in near-infrared spectroscopy (NIRS)-derived deoxygenated hemoglobin and myoglobin concentration ([HHb+Mb] to change in V ̇O2 (Δ[HHb+Mb]/ΔV ̇O2 ) (66).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The impairments in V ̇O2peak in T2D might be influenced by cardiovascular limitations at a systemic level, such as impaired left ventricular filling (68, 69), and limitations in peripheral vasodilation and/or microvascular function in the lower limbs (5,18,19,25,27,32,49,52,65). Regarding peripheral O2 delivery constraints, Kiely et al (26) initially reported reduced peak leg haemodynamic and vasodilatory responses during an incremental calf plantar-flexion exercise in uncomplicated T2D.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical situations radical oxygenation failure is seen classically in cardiovascular shock, rapid blood loss, injury, critical illness or sepsis [2]. There may also be failures of local circulation compromising specific peripheral tissues as in peripheral vascular disease and late diabetes [3]. Measurement of tissue oxygen partial pressure (pO 2 ) has the potential to provide a metabolic 'short-hand' of the balance between the adequacy of a blood supply and cellular oxygenation demand [2].…”
Section: Introductionmentioning
confidence: 99%